LOS CAUTIVOS DE ARGEL DE LOPE DE VEGA Y LA EXPULSIÓN DE LOS MORISCOS. - Ohanna, Natalio (Hispanic Review)
This article presents a literary criticism for the play "Los cautivos de Argel," by Spanish playwright Lope de Vega. The author examines the case of Abdela Alicaxet, a Spanish Muslim who was tried and exiled by the Spanish Inquisition in 1576, which served as a main influence of the work. The representation of the lives of Muslims living in Spain, also known as moriscos, is also explored.